Expression of Inhibitor of Apoptosis Gene Family Members in Bladder Cancer Tissues and the 5637 Tumor Cell Line - Bagrezaei, Fahmideh (Asian Pac J Cancer Prev, 2018)
BACKGROUND: Apoptosis is suppressed in cancer tissues and tumor cell lines because anti-apoptosis genes are over- expressed. The inhibitor of apoptosis proteins (IAP) gene family contributes to control of apoptosis. The expression profile of eight genes of the IAP family in biopsies from patients with a history of bladder cancer and normal bladder tissues, as well as a bladder tumor cell line (5637), was assessed in the present study. METHODS: Cancer tissue samples were obtained at surgery and the 5637 tumor cell line was cultured in RPMI1640 medium. Beyond tumor margins were selected as normal tissue. Expressional profile of interested genes was obtained by using specific primers and the real-time PCR method. RESULTS: The results showed that expression of seven of the studied genes was up-regulated in cancer tissues and the cell line whereas BIRC4 (XIAP) was down-regulated in both. CONCLUSIONS: The results showed that these genes were expressed to a greater extent in cancer tissue and cancer cells than in normal tissues. The data suggested that over-expression of anti-apoptotic genes such as IAP family members, can trigger cells to escape from apoptosis.